Implications of True and Perceived Treatment Burden on Cardiovascular Medication Use. Issue 2 (October 2017) - Sussman, Jeremy B.; Schell, Greggory J.; Lavieri, Mariel S.; Hayward, Rodney A.
Background: Clinical decisions require weighing possible risks and benefits, which are often based on the provider's sense of treatment burden. Patients often have a different view of how heavily treatment burden should be weighted.Objective: To examine how much small variations in patient treatment burden would influence optimal use of antihypertensive medications and how much over- and undertreatment can result from clinicians misunderstanding their patients' values.Methods: Analysis—Markov chain model. Data sources—Existing literature, including an individual-level meta-analysis of blood pressure trials. Target population—US representative sample, ages 40 to 85, no history of cardiovascular disease. Time horizon—Effect of 10 years of treatment on estimated lifetime quality-adjusted life-year (QALY) burden. Perspective—Patient. Outcome measures: QALYs gained by treatment.Results: Fairly small differences in true patient burden from blood pressure treatment alter the number of blood pressure medications that should be recommended and alters treatment's potential benefit dramatically. We also found that a clinician misunderstanding the patient's burden could lead to almost 30% of patients being treated inappropriately.Limitations: Our results are based on simulation modeling.Conclusions: Clinical decisions that fail to account for patient treatment burden can mistreat a very large proportion of the public. Successful treatment choices closely depend on a clinician's ability to accurately gauge a patient's treatment burden.